The Prudential supervision of netting, market risks and interest rate risk : preface to consultative proposal - Basel Committee on Banking Supervision; Bank for International Settlements (Basle Bank for International Settlements, 1993)
This package contains proposals for certain modifications to the Basle Capital Accord of July 1988 which will affect institutions' capital requirements. The market risk proposals could result in a higher or lower aggregate capital requirement, depending on the risk profile of the individual institution. This is because some of the requirements will substitute for existing credit risk requirements. Moreover, banks may have reduced overall capital charges under the netting proposal to the extent that they have legally valid netting arrangements governing their trading in certain financial instruments. The proposals for interest rate risk do not involve capital charges because they adress only teh measurement of interst rate risk
Keywords: International banking; INTERNATIONAL BANKING; MANAGEMENT; RISK MANAGEMENT